1998
DOI: 10.1093/alcalc/33.6.631
|View full text |Cite
|
Sign up to set email alerts
|

Benfotiamine in Treatment of Alcoholic Polyneuropathy: An 8-Week Randomized Controlled Study (Bap I Study)

Abstract: A three-armed, randomized, multicentre, placebo-controlled double-blind study was used to examine the efficacy of benfotiamine vs a combination containing benfotiamine and vitamins B6 and B12 in out-patients with severe symptoms of alcoholic polyneuropathy (Benfotiamine in treatment of Alcoholic Polyneuropathy, BAP I). The study period was 8 weeks and 84 patients fulfilled all the prerequisite criteria and completed the study as planned. Benfotiamine led to significant improvement of alcoholic polyneuropathy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 15 publications
0
35
0
6
Order By: Relevance
“…Safety assessments took into account vital signs at each assessment and occurrence, severity, and duration of any adverse effects, including changes in laboratory tests. These assessments were adopted based on previous clinical studies of alcoholic polyneuropathy (Peters et al 2006;Woelk et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Safety assessments took into account vital signs at each assessment and occurrence, severity, and duration of any adverse effects, including changes in laboratory tests. These assessments were adopted based on previous clinical studies of alcoholic polyneuropathy (Peters et al 2006;Woelk et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…32 Therefore, BoNT-A may be a useful option for painful localized contractures that do not respond to standard treatment. 32 Several studies investigating the effects of benfotiamine (a lipid-soluble derivative of vitamin B1 with high bioavailability) on polyneuropathy have shown significant improvements in vibration perception threshold, 33 nerve conduction velocity, 34 neuropathy score, and pain. 35 These studies highlight the improvements in sensory and motor function in patients with polyneuropathy when treated with mono-or polyvitamin formulations.…”
Section: Discussionmentioning
confidence: 99%
“…The petitioner indicates that out of eleven trials with clinical endpoints, seven (Winkler et al, 1999;Woelk et al, 1998;Haupt et al, 1998;Barkai et al, 1998;Simeonov et al, 1997;Stracke et al, 1996;Ledermann and Wiedley, 1989) explicitly reported no side effects at all or no differences in side effect incidence between active and placebo groups.…”
Section: Benfotiaminementioning
confidence: 99%
“…Most of the controlled trials (Winkler et al, 1999;Woelk et al, 1998;Haupt et al, 1998;Simeonov et al, 1997;Stracke et al, 1996;Ledermann and Wiedley, 1989) also monitored a variety of biochemical parameters, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), gamma-glutamyltransferase (gamma-GT), total and HDL cholesterol, triglycerides, creatine, alkaline phosphatase (ALP), white and red blood cell counts, hemoglobin, sodium, haematocrit, potassium, urea, uric acid, serum protein, and erythrocyte sedimentation rate, urine albumin, sugar and protein, as well as parameters most directly related to diabetic disease state. These trials have consistently shown that there were no statistically significant differences in these parameters between the exposed and control groups.…”
Section: Benfotiaminementioning
confidence: 99%